Case Report: Two cases of atypical neurofibroma neoplasm of uncertain biological potential in the nasal cavity and a literature review - Zhang, Ziyi; Pang, Wenhui; Chen, Min; Jiang, Yan; Zhao, Yuhui; Fu, Shengyao; Wen, Junfeng (Frontiers in Oncology, 2025)
ObjectiveThis study aims to investigate the clinical diagnosis, treatment processes, and pathological characteristics of two cases of atypical neurofibroma neoplasm of uncertain biological potential (ANNUBP) located in the nasal cavity.Materials and MethodsWe retrospectively analyzed the medical history, imaging studies, pathological results, and follow-up data of two patients diagnosed with nasal ANNUBP who were admitted to Qingdao University Hospital between June and October 2023. A review of relevant literature was conducted to summarize their clinical characteristics, diagnosis, treatment, and prognosis.ResultsBoth patients underwent surgical treatment, with one receiving postoperative radiotherapy. Follow-up evaluations indicated that both patients experienced satisfactory recovery, with no signs of local recurrence or distant metastasis.ConclusionANNUBP is a recently recognized and rare subtype of neurogenic tumor. Surgical intervention is regarded as an effective treatment method. This study adhered to established treatment principles for nasal tumors and achieved satisfactory outcomes through surgical intervention and diligent postoperative follow-up.